(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Pregnancy is thus characterized by an anti-inflammatory milieu in the second trimester despite a pro-inflammatory response in the first and third trimesters. Nonetheless a disproportionate inflammatory response is risky in pregnancy. This retrospective study evaluated the mid-gestational expression of inflammatory and anti-inflammatory cytokines in HIV infected pregnant women at their first antenatal visit. Archived serum samples were collected from seventy (n=70) black pregnant women, attending a primary health care centre in KwaZulu-Natal, South Africa. The demographic and clinical profiles were procured from patient medical records and cytokine levels were measured in all samples. A statistical significance (p<0.05) was noted for IP-10 between the HIV positive and HIV negative groups for the inflammatory, anti-inflammatory cytokines and chemokines when stratified by HIV status. Likewise, IL-7 was statistically different when the HIV population was stratified based on ART usuage. Significant correlations were noted between IL-7 and birthweight (r=0.35, p<0.05); IFN-δ and maternal age (r=-0.27, p<0.05); TNF-α and gestational age (r=0.26, p<0.05); VEGF and systolic blood pressure (r=0.40, p<0.05); IL-4 and gestational age (r=-0.30, p<0.05). A positive correlation was noted for inflammatory IL-1b with anti-inflammatory IL-5, IL-5 and FGF basic; inflammatory IL-2 with anti-inflammatory IL-5, IL-10 as well as FGF basic. A negative correlation between the inflammatory IL-12 with anti-inflammatory IL-1ra and Il-4 as well as that between IL-17A with IL-10 was noted. This study reveals midgestational variation in serum inflammatory and anti-inflammatory immunologic profile of pregnant women, irrespective of the use of antiretroviral therapy. This disparity in the susceptible HIV infected women will affect progression of pregnancy and encourage fetal morbidity and mortality.